(Baby)Talk to Me: The Social Context of Infant-Directed Speech and Its Effects on Early Language Acquisition. (October 2015) - Golinkoff, Roberta Michnick; Can, Dilara Deniz; Soderstrom, Melanie; Hirsh-Pasek, Kathy
Since the mid-20th century, scientists have observed unique features in speech, facial expression, and content directed to infants and toddlers in comparison to speech directed to adults. Whereas much research has studied the characteristics of so-called infant-directed speech and speculated about its significance for language learning, research directly testing these ideas has been more limited until recently. Studies now suggest that infant-directed speech (a) promotes infant attention to language, (b) fosters social interaction between infants and caregivers, and (c) informs infants about various aspects of their native language by heightening distinctions relative to the speech addressed to adults. New developments focusing on the social role of infant-directed conversational interactions highlight the importance of caregiver responsiveness to the infant. Building a communicative foundation even prior to the time language emerges is crucial for fostering language development.